Synergy of Transformational Leadership and Improving Managerial Competence of School Principals: A Case Study in State Elementary School 2 Selanegara - Hasanah, Siti Nur; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
The research aims to describe and analyze the synergy between the transformational leadership of the principal and the improvement of his managerial competence at SDN 2 Selanegara. Transformational leadership, characterized by the ability to inspire and motivate teachers and students, is believed to have implications for how principals carry out their managerial functions. Through a qualitative case study approach, data was collected through interviews with principals, teachers, and education staff, as well as observation of school activities and analysis of related documents. The results of the study showed that the transformational leadership practices of school principals at SDN 2 Selanegara, which included providing a clear vision, providing individual support, stimulating intellectually, and providing inspiration, positively correlated with the improvement of managerial competence in planning, organizing, implementing, and supervising school activities. The principal's ability to inspire and motivate staff creates a collaborative and innovative work environment, to facilitate the effective and efficient implementation of school policies and programs. The conclusion is that transformational leadership significantly contributes to strengthening the managerial competence of school principals in managing and developing schools.